Hedonic Gratification Versus Risk Paranoia in the Sharing Economy: The Strategic Architecture of Generation Z Platform Retention - Zahra Zaituna Khalida; Musawer Hakimi; Sheik Mohamed (Yayasan Cerdas Pedia Indonesia, 2026)
The global sharing economy faces a strategic paradox regarding user retention, particularly among Generation Z digital natives who demand immersive hedonic gratification yet simultaneously exhibit extreme risk paranoia. This study aims to structurally map the behavioral architecture of collaborative consumption by evaluating how hedonic value, perceived ease of use, and perceived risk influence behavioral intention through the mediation of consumer attitude. Employing a quantitative explanatory design, primary data was extracted from 400 Generation Z respondents in Central Java, Indonesia, and analyzed using Variance-Based Partial Least Squares Structural Equation Modeling (PLS-SEM). The empirical results demonstrate that hedonic value and perceived ease of use significantly cultivate positive attitudes, whereas perceived risk operates as a systemic cognitive destructor that substantially degrades these affirmative evaluations. Furthermore, attitude functions as the ultimate central mediator that deterministically drives sustainable collaborative consumption intentions. These findings theoretically advance the Stimulus-Organism-Response paradigm by proving that affective stimulation outpaces traditional utilitarian calculus within emerging digital markets. Strategically, this research provides a prescriptive blueprint for platform architects, compelling a managerial pivot toward digital infrastructures that simultaneously neutralize cybersecurity threats and deliver highly gamified experiences to secure long-term commercial viability.